Cinobufacini injection suppresses the proliferation of human osteosarcoma cells by inhibiting PIN1-YAP/TAZ signaling pathway - Chen, Yuru; Wang, Yanyan; Zhai, Yu; Yuan, Ye; Wang, Junhong; Jin, Yajing; Dang, Lingling; Song, Liming; Chen, Changbao; Wang, Yu (Frontiers in Pharmacology, 2023)
Cinobufacini injection (CI), an aqueous extract of Cutis Bufonis, is clinically used for cancer therapy in China, but its molecular mechanism for the treatment of osteosarcoma (OS) remains unclear. We constructed U2OS ectopic subcutaneous tumor model to verify the anti-OS effect of CI in vivo. Meanwhile, cell proliferation of U2OS and MG63 cells was monitored in vitro using the CCK-8 assay, colony formation and morphological changes. Integrated network pharmacology revealed an underlying mechanism of CI in treating OS, which was confirmed by flow cytometry and western blot, which showed that CI significantly inhibited proliferation, induced cell cycle arrest and apoptosis in human OS cells. The further RNA-seq results identified that the Hippo signaling pathway was involved in the anti-OS effect of CI. YAP/TAZ are two major components of the Hippo pathway in breast cancer and are positively regulated by prolyl isomerase PIN1, we assessed their role in OS using both clinicopathological sections and western blots. CI also inhibited PIN1 enzyme activity in a dose-dependent manner, which resulted in impaired PIN1, YAP, and TAZ expression in vitro and in vivo. Additionally, 15 potential compounds of CI were found to occupy the PIN1 kinase domain and inhibit its activity. In summary, CI plays an anti-OS role by down-regulating the PIN1-YAP/TAZ pathway.